2011
DOI: 10.1371/journal.pone.0018147
|View full text |Cite
|
Sign up to set email alerts
|

Assay of the Multiple Energy-Producing Pathways of Mammalian Cells

Abstract: BackgroundTo elucidate metabolic changes that occur in diabetes, obesity, and cancer, it is important to understand cellular energy metabolism pathways and their alterations in various cells.Methodology and Principal FindingsHere we describe a technology for simultaneous assessment of cellular energy metabolism pathways. The technology employs a redox dye chemistry specifically coupled to catabolic energy-producing pathways. Using this colorimetric assay, we show that human cancer cell lines from different org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 45 publications
2
66
0
Order By: Relevance
“…1 and 2). The host metabolic effects we observed upon B. abortus infection resemble the effect of mitochondrial inhibitors (19) and are consistent with the previously reported downregulation of mitochondrion-associated gene expression in macrophages infected with B. melitensis (20). Many bacteria are known to affect host mitochondria (21), but only a few species have been reported to disrupt mitochondrial structure or localization (9,10,22).…”
Section: Discussionsupporting
confidence: 90%
“…1 and 2). The host metabolic effects we observed upon B. abortus infection resemble the effect of mitochondrial inhibitors (19) and are consistent with the previously reported downregulation of mitochondrion-associated gene expression in macrophages infected with B. melitensis (20). Many bacteria are known to affect host mitochondria (21), but only a few species have been reported to disrupt mitochondrial structure or localization (9,10,22).…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of various substrates utilization was performed using PM-M1 and PM-M2 Biolog microplates, coated with different oxidizable carbon sources in various wells, following the manufacturer's instructions (18). Briefly, cells (30 Â 10 3 /well) were plated on Biolog microplate for 24 hours in IFM1 media at 37 C and under 5% CO 2 allowing the cells to use up residual carbonenergy sources.…”
Section: Metabolic Analysesmentioning
confidence: 99%
“…Our in vitro MTS assay demonstrated that tree saps rich in these monosaccharaides facilitated the metabolism of HepG2 cells, whereas sucrose-contacting saps were deprived of this activity. Interestingly, glucose alone, but not sucrose, is able to induce growth of HepG2 cells [28]. Since glucose levels were highly correlated with fructose content across all studied saps, one may expect that fructose also positively affects the growth of HepG2 cells.…”
Section: Discussionmentioning
confidence: 91%
“…Since glucose levels were highly correlated with fructose content across all studied saps, one may expect that fructose also positively affects the growth of HepG2 cells. In fact, it has been previously demonstrated that HepG2 cells are able to utilize fructose as energy source [28].…”
Section: Discussionmentioning
confidence: 99%